Mitigation techniques to reduce avian electrocution rates. (14th August 2019) - Dixon, Andrew; Rahman, MD Lutfor; Galtbalt, Batbayar; Bold, Batbayar; Davaasuren, Batmunkh; Batbayar, Nyambayar; Sugarsaikhan, Batkhuu
ABSTRACT: From August 2013, we undertook a 1‐year trial of mitigation techniques at an electricity power line in the Mongolian steppe with a high avian electrocution rate. We examined 2 mitigation methods at phase‐1 conductors on the top of power poles (i.e., reconfiguration of the insulator mount and insulation covers on the conductor wire) and 3 mitigation methods at phase‐2 and 3 conductors on pole cross‐arms (i.e., perch deflector brushes, rotating‐mirror perch deterrents, and insulation covers on the conductor wires). The perch management techniques selected for the trial are currently widely adopted by power line managers in Mongolia. In comparison with the control, with no mitigation, electrocution rates were reduced both by the reconfiguration of insulator mounts and insulation of conductor wires at phase‐1, though the reduction was greater for the former—73% mean reduction for reconfigured mounts and 59% for insulation covers. Electrocution rates were reduced by the placement of rotating‐mirrors and insulation of conductor wires at phases 2 and 3, with the reduction being greater for the former—91% mean reduction for mirrors and 66% for insulation covers. Deployment of metal perch deflector brushes at phases 2 and 3 had no effect on electrocution rates and should not be used as mitigation. Most electrocutions occurred at phase 1 on the top of the pole, indicating that mitigation should be prioritized at this phase. In terms of cost and efficacy, reconfigured mounts represented the best option as a permanent fix at phase 1. At phases on cross‐arms, the relative merits of mirrors and insulation covers need to be assessed over a longer period, and these temporary mitigation measures should be compared with alternative permanent fixes. © 2019 The Wildlife Society. Abstract : We examined the efficacy of different mitigation methods aimed at reducing raptor electrocution rates at a power distribution poles in Mongolia. Cover‐up insulation on live conductors, reconfiguration of pin‐insulator mounts at the top of the pole and rotating mirror perch deterrents all reduced electrocution rates, whereas metal brush perch deflectors on the crossarm did not.